Pengaruh Komite Audit, Kualitas Audit, dan Konservatisme Akuntansi terhadap Tax Avoidance - Angela Merici S.T. Tahilia; Sulistyowati Sulistyowati; Said Khaerul Wasif (Jurnal Manajemen, 2022)
This study aims to examine the influence of the Audit Committee, Audit Quality, and Accounting Conservatism on Tax Avoidance in Consumer Goods sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The method used in this study is associative with a form of causal relationship with a quantitative approach. The population used in this study was 75 Consumer Goods sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The selected samples based on the purposive sampling method were 11 companies. The data used is secondary data. The collected data was analyzed using the Eviews 9 program. Based on the results of processed data, the results of this study show that 1) The Audit Committee has a positive and significant influence on Tax Avoidance 2) Audit Quality has a positive and significant influence on Tax Avoidance, while 3) Accounting Conservatism does not have a significant influence on Tax Avoidance.